Perbandingan Manajemen Utang Sri Lanka dan Indonesia Terhadap World Bank (Bank Dunia) - Isna, Nurhana Putri; Ramadhani, Rizki Dhiya; Margaretha, Tiur; Mulalugina, Shangra; Amin, Fikri Fakhrial; Athfal, Delliq Hastariq; Yuningsih, Neneng Yani (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Sri Lanka and Indonesia are two countries that have a large debt relationship, the complexity of international debt management. Both must confront a variety of policies and strategies to deal with their debt, including issues such as interest rates, terms, payment structures, and political and economic impacts. Rising debt is often part of ambitious economic development strategies, but can raise concerns about long-term financial sustainability. State debt management is the process of managing the debt owned by a country. The main goal is to ensure the sustainability of state finances and prevent crises that could harm the economy as a whole (Aribowo et al., 2023). The Debt Management Office (DMO) is one approach that the Sri Lankan and Indonesian governments can use to manage debt more effectively. By using DMO, both countries can manage their debt more efficiently, improve financial sustainability and reduce the risks associated with external debt. A comparison between Sri Lanka and Indonesia shows that a strong and independent DMO approach is essential for effective and sustainable debt management.